SISTEM INFORMASI PEMILIHAN PUTRA PUTRI UNIVERSITAS PGRI KANJURUHAN MALANG - Green Calvin; Hari Lugis Purwanto; Gaguk Susanto (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2023)
Abstract.This study focuses on discussing the results of research on Male and Female Electoral Information Systems at PGRI University Kanjuruhan Malang. The process of registration and selection of campus ambassadors at PGRI Kanjuruhan University in Malang is still being done manually. At the registration stage, the committee was faced with the problem of downloading data and overlapping data. At the administrative selection stage, the committee found it difficult to see the profiles of the participants because they had to open the physical files one by one. Interview tests, written tests and interest and aptitude tests require a long time because the system still manual, so you have to be really careful and thorough. Therefore the authors conducted research that utilizes existing technology to deal with this. The systemized process of selection and selection is able to carry out the process of registering prospective participants and the selection process that is faster than the manual process. Measurement of the feasibility level of the application was carried out by using the completed User Acceptance Test (UAT) to get 89.17% results from 30 respondents who agreed that the system was able to make it easier for the selection committee and prospective campus students.